ALGORITHM A* FOR THE NEAREST ROUTE TRACKING SYSTEM IN THE MODE OF TRASNPORTATION - Febri Ramanda; Eko Sediyono; Catur Edi Widodo (Jurnal Ilmiah Kursor, 2019)
Transport as a basic services industry as the basis of national economic development, it is the foundation of a nation's progress. With increasing in the standard life society, transportation needs for the whole society have also increased. Online transportation service needs are influenced by various factors such as cost, quality of service, income and ownership that modes of transport used. The purpose of this study is to apply the A* algorithm to find paths or routes, because it is quite flexible and works better than the algorithm dijakstra in all cases (barriers and without obstacles). The results showed that the A* algorithm is able to provide the information than other algorithms that are best finding the shortest path.